ANALYSIS OF THE UTILIZATION OF COMPETENCY ASSESSMENT RESULTS FOR FUNCTIONAL AUDITOR POSITIONS IN THE AUDIT BOARD OF THE REPUBLIC OF INDONESIA - Novi Priyana*; Bambang Giyanto; Ridwan Rajab (Jurnal Apresiasi Ekonomi, 2024)
This study aims to analyze the utilization of competency assessment results for functional auditor officials at the Auditorate General of Audit V, The Audit Board of The Republik of Indonesia (BPK). The research examines how competency assessment results are utilized in career development, competency enhancement, and the assignment of functional auditor officials at BPK. The study employs a qualitative descriptive method with informants from HR management, structural officials in technical examination units, and stakeholders of functional auditor positions. Primary and secondary data were collected through interviews, observations, and documentation, subsequently analyzed using data reduction analysis techniques. The research findings indicate that BPK has systematically and objectively implemented competency assessments. These competency assessment results are used for objective career development, targeted competency enhancement, and as guidelines in assigning functional officials, thereby enhancing their professionalism. This study contributes to the discourse on the utilization of competency assessments as part of talent management at BPK, particularly in the management of functional positions. The implications of this research underscore the importance of using competency assessments as instruments to support strategic decision-making related to career development and HR management within government institutions.Keywords: competency assessment, functional positions, human resource management